Smart Air Quality Monitoring System in Realtime using IoT - et. al., Vimal Kumar M N, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As the countries become industrial, the pollution level to our environment is increase and this becomes a significant downfall for the health of people and additionally affects the scheme. In this paper a model based on IOT is proposed with the aim to monitor pollution level. The most serious environment pollution is air pollution because diverse air pollutant causes harm to human health and causes global warming. The pollution monitoring system is extremely vital to keep away from such adverse imbalance in nature. With the speedy growth in the industries which are the main sources of pollutants, the problem of pollution is becoming a serious concern for the health of the population. The proposed outline includes a set of sensors like gas sensors, noise detector, fire sensor and ultrasonic sensor as hardware having Arduino platform with the combination of software architecture for remotely monitoring the pollution information through one web-based graphical malicious program.